Assistance for Innovative Scientific Work of MGMP of Social Studies Teachers - Thriwaty Arsal; Dewi Liesnoor Setyowati; Puji Hardati; Hamdan Tri Atmaja (Social Studies Conference Proceedings, 2022)
One of the competencies that teachers need to improve is professional competence. One indicator of a professional teacher is an increase in the ability to develop knowledge, especially in writing innovative scientific publications such as research work, thoughts or ideas, popular scientific articles, and journal articles. In this regard, teachers need to participate in PKB training for the Development of Innovative Teacher Work. This training aims to enable teachers to improve their professionalism as professional teachers, ultimately impacting the quality of education in Indonesia. Therefore it is deemed necessary to hold community service for forms of innovative scientific publication training for social studies teachers at SMAN 13 Semarang and the obstacles and constraints of teachers in innovative scientific publication training. The objectives of this activity are Socialization in the form of providing reference knowledge about efforts and innovative scientific publication training for social studies teachers with the mentoring method is carried out by delivering material related to innovative scientific article writing techniques and the rules of the environment in several scientific journals, both those that have not been accredited and those that have been accredited.